Giant transposons promote strain heterogeneity in a major fungal pathogen - Emile Gluck-Thaler; Adrian Forsythe; Charles Puerner; Cecilia Gutierrez-Perez; Jason E. Stajich; Daniel Croll; Robert A. Cramer; Aaron A. Vogan (mBio)
ABSTRACT Fungal infections are difficult to prevent and treat in large part due to strain heterogeneity, which confounds diagnostic predictability. Yet, the genetic mechanisms driving strain-to-strain variation remain poorly understood. Here, we determined the extent to which Starships—giant transposons capable of mobilizing numerous fungal genes—generate genetic and phenotypic variability in the opportunistic human pathogen Aspergillus fumigatus. We analyzed 519 diverse strains, including 11 newly sequenced with long-read technology and multiple isolates of the same reference strain, to reveal 20 distinct Starships that are generating genomic heterogeneity over timescales relevant for experimental reproducibility. Starship-mobilized genes encode diverse functions, including known biofilm-related virulence factors and biosynthetic gene clusters, and many are differentially expressed during infection and antifungal exposure in a strain-specific manner. These findings support a new model of fungal evolution wherein Starships help generate variation in genome structure, gene content, and expression among fungal strains. Together, our results demonstrate that Starships are a previously hidden mechanism generating genotypic and, in turn, phenotypic heterogeneity in a major human fungal pathogen.IMPORTANCENo “one size fits all” option exists for treating fungal infections in large part due to genetic and phenotypic variability among strains. Accounting for strain heterogeneity is thus fundamental for developing efficacious treatments and strategies for safeguarding human health. Here, we report significant progress toward achieving this goal by uncovering a previously hidden mechanism generating heterogeneity in the human fungal pathogen Aspergillus fumigatus: giant transposons, called Starships, that span dozens of kilobases and mobilize fungal genes as cargo. By conducting a systematic investigation of these unusual transposons in a single fungal species, we demonstrate their contributions to population-level variation at the genome, pangenome, and transcriptome levels. The Starship compendium we develop will not only help predict variation introduced by these elements in laboratory experiments but will serve as a foundational resource for determining how Starships impact clinically relevant phenotypes, such as antifungal resistance and pathogenicity.